Vulvodynia: epidemiology, etiology and classifications. Part 1 - Wachowska, Katarzyna; Florkowski, Antoni; Orzechowska, Agata; Talarowska, Monika; Berent, Dominika; Depko, Andrzej; Moczulska, Hanna; Michalska, Tamara; Gałecki, Piotr (Menopause Review/Przegląd Menopauzalny, 2012)
Vulvodynia is a chronic disorder involving pain or discomfort characterized by a feeling of burning, stinging or irritation in the female genitalia in cases where there is no infection or skin disease of the vulva or vagina causing these symptoms. Vulvodynia is a clinical syndrome, which according to current estimates, can occur in 15% of women. Clinical observations indicate the existence of different subtypes of vulvodynia, distinguished based on their etiology. The multidimensional impact of this disease on the functioning of women is indicated, yet there are no clear answers as to its etiology, effective treatments, prevention and dissemination. The authors review the most important information about vulvodynia and currently used diagnostic criteria. Various theories about the etiology of the disease are presented, focusing mainly on factors such as: biological, developmental, genetic, immunological, hormonal, neurological and psychological ones. The article also presents data on the prevalence of vulvodynia in the population. Presented data are derived from researches conducted by various scientists. The authors present the proposed classifications of vulvodynia types, made on the basis of its etiology and characteristics of pain experienced by patients. Attention should be paid to the difficulties in unambiguous classification of patients to a group suffering from vulvodynia. The impact of this disease on the psychosocial functioning of patients and the difficulties encountered when seeking effective help are also underlined.